A miniaturized flexible surface attachable interrogator for hybrid optical fiber sensing. Issue 5 (May 2014) - Ramakrishnan, Manjusha; Rajan, Ginu; Semenova, Yuliya; Wolinski, Tomasz; Domański, Andrzej; Farrell, Gerald
ABSTRACT In this article, we propose a miniaturized flexible interrogator for polarimetric and fiber Bragg grating (FBG) sensors based hybrid sensing scheme embedded in composite materials. The flexible interrogation module comprises of an arrayed waveguide (AWG) for FBG demodulation and an electro optic mach–zehnder interferometric (EO‐MZI) intensity modulator for polarimetric sensor demodulation. A customized design of AWG and EO‐MZI are presented, and the designed performance resulted in a wide channel spacing of 5 nm and low cross talk of −34 dB between adjacent channels for the AWG, and a low Vπ voltage of ±1.5 V for the MZI‐EO. The method for fabrication of the flexible interrogator device is also presented, based on post processing of platinum coated polyimide substrate. The film type interrogation module is compact, with a size of 3.4 × 0.1 × 0.01 cm3. The surface attachable flexible hybrid sensor interrogator is proposed to integrate with photo detector arrays and wireless communication technology to enhance the competency of hybrid sensing scheme in smart sensing composite parts in motion for applications in aircraft, wind rotor blades and so forth. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1167–1174, 2014